Geografia do trabalho no Brasil - Alexandre Gori Maia (Confins)
The purpose of this paper is to examine the territorial configuration of the labor market in Brazil, analyzing the distribution of its municipality occupational structures. The main idea is that the occupational structure, a combination between the labor market position (occupational class) and wage class intervals (economic stratum) plays an important role in examining the municipality stage of socio-economic development and the extreme inequalities of the Brazilian territory. The individual’s occupation defines his occupational class, which is identified in terms of its political power, social prestige and capability to generate income. Considering the extreme wage inequalities in Brazil, even among members of relatively homogeneous occupational classes, it is also defined a second criterion of classification, the economic stratum, using wage class intervals of the major occupation. The analyses are based on information provided by 2000 Demographic Census, correspondence and cluster multivariate statistical techniques, and on the spatial distribution of municipalities in a coropletic map. Although the obtained classification does not allow quantifying the relation between Brazilian municipalities, it allows identifying an obvious socio-economic hierarchy among groups of municipalities. Overall, most Brazilian municipalities show low pattern of socio-economic development, prevailing agricultural activities and a huge number of low-paid workers. The few more developed urban municipalities concentrate most of the Brazilian population and, though presenting a higher participation of employees in top economic stratums, they share most of excluded persons in Brazil. The more contiguous area of high developed counties occurs close to the two main Brazilian states, São Paulo and Rio de Janeiro, apart from important areas of development close to the coast. The less developed rural municipalities prevail in the semi-arid areas of the country, in the Amazon rain forest and close to the triple border with the Mercosur countries.